Pengaruh Pop Up Book Animasi Terhadap Pemahaman Konsep Pada Materi Komponen Ekosistem Siswa Kelas V Di SD Negeri 005 Rambah - Nauli Tama Sari; Ari Aprilia Dwiana (Jurnal Teknologi Informasi (JUTECH), 2025)
Education is a tool to build a better nation and state. Learning is an interaction process between students and teachers. The learning process takes place between components that are interrelated with each other with the content of educational goals. The teacher is the most influential component to the creation of quality educational processes and outcomes. his quantitative research method is a quasi-experimental method, a quasi-experiment is a research that approaches an experiment where it is impossible to control/manipulate all relevant variables. n this research, the researcher used a quasi-experimental model which was conducted in two classes, namely the experimental class and the control class. The result of Equal Variances Assumed from understanding the concept with a sig.(2-tailed) value is 0.000. Based on the decision making criteria sig.(2-tailed) 0.000 0.05 then H0 is rejected and Ha is accepted. The results of Equal Variances Assumed from interest in learning with a sig.(2-tailed) value is 0.000. There is a significant effect of the use of animated pop up book media on students' understanding of concepts in science subjects in class V SD Negeri 005 Rambah. Based on the results of the T-Test test analysis in the experimental class, it was obtained a sig (2-tailed) value of 0.000 0.05, it can be concluded that the animated pop up book media has a positive effect on conceptual understanding at SD Negeri 005 Rambah